2002
DOI: 10.1046/j.1095-8312.2002.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of adhesive mechanisms in cribellar spider prey capture thread: evidence for van der Waals and hygroscopic forces

Abstract: Sticky prey capture threads are produced by many members of the spider infraorder Araneomorphae. Cribellar threads are plesiomorphic for this clade, and viscous threads are apomorphic. The outer surface of cribellar thread is formed of thousands of fine, looped fibrils. Basal araneomorphs produce non‐noded cribellar fibrils, whereas more derived members produce noded fibrils. Cribellar fibrils snag and hold rough surfaces, but other forces are required to explain their adherence to smooth surfaces. Threads of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 23 publications
1
44
0
1
Order By: Relevance
“…Thus, we believe that there is maximum contact between cribellar fibrils and this surface. At a relative humidity (RH) of around 50%, noded cribellar thread sticks to this surface with a force comparable to that with which it holds fleshfly wings (Hawthorn and Opell, 2002). Thus, measured forces are in the range of those registered by a representative insect surface.…”
Section: Measuring Thread Stickinessmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, we believe that there is maximum contact between cribellar fibrils and this surface. At a relative humidity (RH) of around 50%, noded cribellar thread sticks to this surface with a force comparable to that with which it holds fleshfly wings (Hawthorn and Opell, 2002). Thus, measured forces are in the range of those registered by a representative insect surface.…”
Section: Measuring Thread Stickinessmentioning
confidence: 67%
“…In a recent study (Hawthorn and Opell, 2002), we demonstrated that, when tested with a smooth surface, cribellar threads formed of non-noded fibrils registered the same stickiness under low and high humidity. By contrast, threads formed of noded fibrils registered greater stickiness under high humidity.…”
mentioning
confidence: 99%
“…Instead of aqueous glue, the axial fibers of cribellate capture silk are surrounded by puffs of tiny cribellar fibrils that can be as thin as 10·nm in diameter (Peters, 1984;Peters, 1992). Although cribellar fibrils are dry, they achieve stickiness through a combination of van der Waals and hygroscopic forces (Hawthorn and Opell, 2002;Hawthorn and Opell, 2003) that allows cribellar fibrils to adhere to even very smooth surfaces (Opell, 1994a).…”
Section: Introductionmentioning
confidence: 99%
“…The key to the structure of the spider protein repeating sequences (fibroins) is the combination of crystal-forming blocks (β-sheet crystals) and amorphous (sometimes helical) network chains that are part of the amino acid sequence motifs [1][2][3]. For instance, the percentages of alanine, glycine and proline affect the degree of crystallinity, helicity (amorphous structure) [4,5], elasticity [6,7], hygroscopicity and adhesiveness [8].…”
Section: Introductionmentioning
confidence: 99%